2020
DOI: 10.31661/gmj.v9i0.1767
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Serotonin Hydrochloride on Adiponectin, Ghrelin and KiSS1 Genes Expression

Abstract: Background: Serotonin and kisspeptin stimulates gonadotropin-releasing hormone (GnRH) and luteinizing hormone (LH) release while ghrelin and adiponectin inhibit them. In the present experimental study, the effects of central injection of serotonin were investigated on LH concentration, KiSS1, adiponectin, and ghrelin genes expression. Materials and Methods: Fifteen Wistar male rats in three groups received saline or serotonin hydrochloride via the third cerebral ventricle. Blood samples were collected via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Furthermore, Kiss1r mRNA was highly increased in the hypothalamus, hippocampus and cerebellum by 170%, 177% and 131%, respectively ( 92 ). Indeed, these findings are congruent with a previous study demonstrating that intra-cerebroventricular injections of serotonin hydrochloride to male rats significantly enhances hypothalamic kisspeptin expression and resultant circulating LH concentrations ( 93 ). Collectively, these data garner further evidence for the interplay between kisspeptin and the serotonergic system in eliciting antidepressant actions, as well as evidence for the putative brain regions involved.…”
Section: Mood and Emotionssupporting
confidence: 91%
“…Furthermore, Kiss1r mRNA was highly increased in the hypothalamus, hippocampus and cerebellum by 170%, 177% and 131%, respectively ( 92 ). Indeed, these findings are congruent with a previous study demonstrating that intra-cerebroventricular injections of serotonin hydrochloride to male rats significantly enhances hypothalamic kisspeptin expression and resultant circulating LH concentrations ( 93 ). Collectively, these data garner further evidence for the interplay between kisspeptin and the serotonergic system in eliciting antidepressant actions, as well as evidence for the putative brain regions involved.…”
Section: Mood and Emotionssupporting
confidence: 91%
“…Studies on Iranian adults from 2001 to 2015 indicated that 43% of Iranian people suffer from varying degrees of depression [9]. Among different treatments proposed for depression, the most common ones are tricyclic drugs such as imipramine and amitriptyline, with side effects like drowsiness, agitation, tachycardia, and weight gain [10]. Also, selective serotonin reuptake inhibitors such as fluoxetine and citalopram with nausea and headache as side effects are used [11].…”
Section: Introductionmentioning
confidence: 99%